1994
DOI: 10.2307/3398728
|View full text |Cite
|
Sign up to set email alerts
|

Music Teaching Style Ideas and Implications

Abstract: looks at dimensions of music teaching style and at how teachers can understand and adjust their style to balance personal, curricular, and student needs. * A A S T he term "teaching style" has been used by educators to mean a number of things, such as specific, effective teaching behaviors, traits related to personality, ways of matching student learning styles, and the interpersonal skills of a teacher. Which is it? The answer is that teaching style is not just one thing, but rather several things that func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Common examples include lack of support or recognition by school leaders (Hamann et al, 1987), burdensome workloads and class scheduling conflicts (Heston et al, 1996), inadequate compensation (Scheib, 2004), and lack of agency/decision-making power (Hamann & Gordon, 2000). Researchers reported burnout also stems from challenges specific to music teaching, such as classroom management issues (Gumm & McLain, 2013), large enrollments inherent to ensemble instruction (Gordon, 2000), and clashing curricular ideologies (Hamann et al, 1987; Scheib, 2006). Music teachers who perceive gaps in their pedagogical knowledge or who otherwise feel unprepared for their teaching assignment often experience a greater degree of burnout (Ballantyne & Retell, 2020; Gordon, 2000).…”
Section: Sources and Symptoms Of Music Teacher Burnoutmentioning
confidence: 99%
See 2 more Smart Citations
“…Common examples include lack of support or recognition by school leaders (Hamann et al, 1987), burdensome workloads and class scheduling conflicts (Heston et al, 1996), inadequate compensation (Scheib, 2004), and lack of agency/decision-making power (Hamann & Gordon, 2000). Researchers reported burnout also stems from challenges specific to music teaching, such as classroom management issues (Gumm & McLain, 2013), large enrollments inherent to ensemble instruction (Gordon, 2000), and clashing curricular ideologies (Hamann et al, 1987; Scheib, 2006). Music teachers who perceive gaps in their pedagogical knowledge or who otherwise feel unprepared for their teaching assignment often experience a greater degree of burnout (Ballantyne & Retell, 2020; Gordon, 2000).…”
Section: Sources and Symptoms Of Music Teacher Burnoutmentioning
confidence: 99%
“…Older, more experienced music educators were found to be less prone to burnout (Bernhard, 2006; Hamann, 1986), especially if they spent seven years or more on the job (Hedden, 2005). Gumm and McLain (2013) discovered that teachers with noncontrolling, student-centered teaching styles reported lower burnout. Çevik Kiliç (2018) found that music teachers who were more extroverted, conscientious, agreeable, and open were less susceptible to burnout, and those who were more neurotic, anxious, impatient, or pessimistic were increasingly susceptible.…”
Section: Sources and Symptoms Of Music Teacher Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when sampling across a wider range of directors, findings appeared less consistent. In an earlier stage of the same study, Bazan administered a self-reported survey involving 49 middle school band directors from Ohio using a revised version of Gumm’s (2004) Music Teaching Style Inventory. Cronbach’s alpha for the Music Teaching Style Inventory was .80, indicating the inventory items were internally consistent.…”
Section: Time Spent Teaching Conceptsmentioning
confidence: 99%
“…Consequently research is usually directed at the auditory level, with performance being the product and evidence of learning (Abeles, Gof & Levasseur, 1992;Gillespie, 1991;Gumm, 1994). For instance, evaluation of the musical product or performance is often used to create assumptions about the effectiveness and extent of teaching or learning.…”
Section: Introductionmentioning
confidence: 99%